Secrets of the sea - Baker, Kate, 1949- (Big Picture Press, 2017)
Traveling from the rock pools of the shoreline to the deepest depths of the ocean, a blending of illustrations and facts about marine animals provides an introduction to some of the ocean's rarely seen creatures.